Maximização da síntese de carotenoides mediante a fotoestimulação do crescimento da microalga Tetradesmus sp - Gonçalves, Vanessa Daneluz (2019)
This research aimed to maximize the carotenoids production of Tetradesmus sp. by photostimulation in different spectral bands (visible, red, yellow, green and blue) and luminous intensities (13 to 595 μmol m-2 s-1). The effect of the factors: light intensity, photoperiod, pH, NaCl and nitrogen concentrations in the response of carotenoids (astaxanthin, β-carotene and lycopene) were evaluated using the Plackett-Burman experimental design. With Central Composite Rotatable Design, regression models were fitted with the factors, which were optimized to predict maximum carotenoid response. Among the results, ANOVA (α = 0.05) suggested a higher synthesis of carotenoids in Tetradesmus sp. under the spectral combination red: green (50%: 50%) in the intensity of 50 μmol m-2 s-1, where high production of carotenoids (6.09 ± 0.29 mg g-1). In the Plackett-Burman experimental design, effects of light intensity and photoperiod were observed (α = 0.10). The adjusted models with these factors presented coefficient of determination between 0.90 ≤ R² ≤ 0.95. The optimization resulted in maximum values of carotenoids in mg g-1, with the cultivation of Tetradesmus sp. under 85 μmol m-2 s-1 of light intensity and 15.8:8.2 h (light:dark) of photoperiod, and maximum carotenoid production in mg L-1 under 595 μmol m-2 s-1 for 24 h. The experimental validation of the values predicted by the models resulted in the synthesis of 7.6 mg g -1 astaxanthin, 9.1 mg g-1 β-carotene and 4.8 mg g-1 lycopene; as well as the production of 12.1 mg L-1 astaxanthin, 12.8 mg L-1 β-carotene and 5.5 mg L-1 lycopene. All results remained within the 95% confidence interval calculated for the values predicted by the models. This work showed an innovative strategy in the research segment with microalgae, with promising results in terms of industrial application, due to the increase in the synthesis of carotenoids by Tetradesmus sp. of 1.67 mg g-1 determined in the preliminary studies, to those obtained at the end of the optimization process.